Remembering with Respect: History, Social Memory and the Cross-Border Journeys of a Charismatic Lue Monk - Wasan Panyagaew (2018)
For over three decades, people's mobility in the borderlands of the upper Mekong region has been reactivated, but simultaneously regulated, by changing state policy. Since the 1990s greater regional cooperation between China and mainland southeast Asian countries in trade and development has resulted in massive and accelerated flows of culture, commodities, capital and information across the borders. This article traces the cross-border movements of one charismatic Buddhist monk, Phra Khru Weruwanpithak (1929-2005), which took place over two decades from the early 1980s to the beginning of the twenty-first century. I argue that this monk's journeys played a significant role in Theravada revivalism in the localities he visited, both in his hometown in northern Thailand, and in other Lue communities in the eastern Shan state of Burma and in Sipsong Panna in southwest China. The practical, religious and architectural activities undertaken by this border-crossing monk not only restored Theravada Buddhist sites in the region, but also created a new sense of place and belonging among the Lue, who have long lived across national borders in the upper Mekong region. © 2013 Copyright The Australian National University.